Effects of Different Adjuvants on the Protective Efficacy of a Subcellular Vaccine Against Chlamydia abortus Infection in Sheep - Morag Livingstone; Kevin Aitchison; Javier Palarea-Albaladejo; Sergio Gastón Caspe; Clare Underwood; Holly Hill; Cameron Cunnea; Kelly Stronach; Francesca Chianini; Gary Entrican; Sean Ranjan Wattegedera; David Longbottom (Vaccines, 2025)
Background/Objective: Recently, we published three studies describing the development and optimization of a new, safe, and efficacious vaccine to protect sheep from ovine enzootic abortion, which is caused by the zoonotic pathogen Chlamydia abortus. The vaccine, which can be delivered through a single inoculation, is based on a detergent-extracted outer membrane protein (chlamydial outer membrane complex or COMC) preparation of the pathogen. This study aimed to optimize the vaccine further by comparing the effects of different adjuvants on protective efficacy. Methods: We evaluated the effectiveness of three different vaccines (2.5 µg COMC) formulated with one of three adjuvants (Montanide ISA 70VG, Montanide ISA 61VG, and QuilA) to reduce the rate of abortion, placental load and pathology, and post-partum vaginal shedding of organisms in comparison to our benchmark 20 µg COMC/Montanide ISA 70 VG vaccine and a challenge control group of animals. The humoral and cellular immunological responses to vaccination and to challenge were also assessed. Results: The two low-dose Montanide formulated vaccines resulted in low abortion rates of 3.2 and 8.1% for ISA 70 VG and ISA 61 VG, respectively, which were comparable to the benchmark vaccine group (2.7%) and considerably lower than the QuilA (23.7%) and challenge control (36.8%) groups. Similarly, the Montanide-adjuvanted groups had much lower bacterial loads (range: 136–431 genome copies) on vaginal swabs post-parturition than the QuilA (8.9 × 104 copies) and challenge control (2.4 × 105 copies) groups. Conclusions: The results showed that both Montanide adjuvants are more effective for maximizing COMC vaccine efficacy than the QuilA adjuvant and result in much lower bacterial shedding of the pathogen post-parturition, which is important for minimizing potential transmission to naïve animals.